Ovulation and fertilization rate of gilts provided additional L-carnitine and chromium nicotinate - Samland, C.J.; Musser, R.E.; Peters, J.K.; Sawyer, J.T.; Owen, K.Q.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We determined the effects of L-carnitine (200 ppm), chromium nicotinate (CrNic; 200 ppb), a combination of L-carnitine and CrNic, or flushing (11 Ibid of complete diet fed for 14 d prior to breeding) on ovulation and fertilization rates in gilts. All gilts (n = 105) were administered PG600 to aid in the synchronization of estrus. After detection of estrus, gilts were assigned randomly to dietary treatments and were fed at 4 Ibid with the exception of gilts on the flushing treatment. Treatments were continued until breeding at the third estrus. Surgeries were performed on d 2 to 3 after third estrus was detected to determine ovulation rate and collect embryos and unfertilized eggs. An increase (P<.10) in ovulation rate was observed for gilts in the flushing or L-carnitine treatment. Supplemental L-carnitine decreased (P =.10) fertilization rate of embryos recovered. No differences were observed for number of empty zonae or number of unclassifiable eggs. Increased ovulation rates for L-carnitine-treated gilts warrants further evaluation to determine whether L-carnitine increases number of pigs farrowed.
Keywords: Swine; L-Carnitine; Chromium; Ovulation; Gilts